Puerarin Attenuates the Cytotoxicity Effects of Bisphenol S in HT22 Cells by Regulating the BDNF/TrkB/CREB Signaling Pathway - Meilin Qin; Xinxin Guo; Nuo Xu; Yan Su; Mengfen Pan; Zhengbao Zhang; Huaicai Zeng (Toxics)
Bisphenol S (BPS) is a widespread environmental endocrine disrupter that can cause hepatotoxicity, neurotoxicity and negative effects on reproduction. Puerarin (PUE) has been found to have anti-inflammatory, antioxidant, and neuroprotective properties, however, its potential protective effects against BPS-induced neurotoxicity and the underlying mechanisms are still not fully understood. In this study, HT22 cells were exposed to different concentrations of BPS with or without PUE. Cell viability, apoptosis, oxidative damage, and the expression level of axon-injury-related genes and the BDNF/TrkB/CREB pathway were analyzed. The results showed that 40 μM to 180 μM BPS and 100 μM to 180 μM PUE significantly decreased the cell viability of HT22 cells, but in the 80 μM PUE group, the cell viability was higher than control group, and the ratio of 1.1. Meanwhile, BPS increased the production of ROS and MDA but decreased the GSH and SOD. However, supplementation with PUE was alleviated the oxidative damage. PUE also alleviated the apoptosis rate that induced by BPS. Additionally, BPS decreased the expression levels of mRNA and proteins of synaptic-related genes, but inhibited the expression levels of mRNA and proteins of the BDNF/TrkB/CREB signaling pathway. Interestingly, PUE was found to significantly recover the expression of synaptic related genes, but also upregulated the expression of the BDNF/TrkB/CREB pathway. In conclusion, our study proved that PUE can attenuate the neurotoxicity effect of bisphenol S, which related to oxidative damage in HT22 cells by regulating the BDNF/TrkB/CREB signaling pathway. This study is not only the first to demonstrate that PUE can mitigate BPS-induced neurotoxicity through oxidative stress modulation, but also provides a novel therapeutic approach involving the BDNF/TrkB/CREB pathway. These findings offer promising insights into natural-based strategies for protecting against environmental neurotoxins and provide a foundation for future therapeutic developments targeting BPS-induced neurotoxicity.